Forecasting of Bull Carcasses Prices for the Future with Box-Jenkins Models: The Case of Tokat Province - Çelik, Mehmet; Arıkan, Mehmet Saltuk (Kastamonu Üniversitesi, 2024)
Aim to study: The purpose of this study is to make future forecast of bull carcass meat prices in Tokat province using econometric methods. It is aimed to analyze bull carcass prices in Tokat province with time series analysis and estimate these prices for 2025. Material and methods: The data set of the study consists of monthly bull carcass prices slaughtered between June 2018 and May 2024. The estimates were made with the Box-Jenkins method, one of the econometric analysis methods. Results: As a result of the time series analysis, the most suitable model for bull carcass prices was determined as ARIMA (0,1,0) (1,1,0). According to the estimation results of bull carcass prices in line with the determined ARIMA models, it was estimated that the bull carcass price in Turkey would reach an average of 550.37 TL/kg in the May 2025 period. Conclusion: In conclusion, time series analysis can be utilized to forecast future bull carcass prices, though these estimates should be regularly updated. This approach can support the future planning efforts of both producers and consumers.
Keywords: Veterinary Sciences (Other); Veteriner Bilimleri (Diğer)